Does age matter? A comparison of health‐related quality of life issues of adolescents and young adults with cancer. (28th November 2018) - Sodergren, Samantha C.; Husson, Olga; Rohde, Gudrun E.; Tomaszewska, Iwona M.; Griffiths, Helen; Pessing, Aya; Yarom, Noam; Hooker, Louise; Din, Amy; Darlington, Anne Sophie; ,
Abstract: Objective: Health‐related quality of life (HRQoL) concerns of adolescents and young adults (AYAs) aged 14–25 years were compared with those of older adults (26–60 years) with cancer. Methods: AYAs and older adults receiving curative intent treatment or supportive palliative care for cancer were recruited from eight research centres across Europe. Participants used a rating scale to score the relevance and importance of a list of 77 issues covering 10 areas of HRQoL concern: symptoms; activity restrictions; social; emotional; body image; self‐appraisals; outlook on life; lifestyle; treatment‐related and life beyond treatment. Results: HRQoL issues were reviewed by 33 AYAs and 25 older adults. Several issues were recognised as relevant and important across all age groups: symptoms, emotional impact, outlook on life, lifestyle and treatment‐related. A number of issues were more relevant or important to AYAs including interrupted education, greater motivation to achieve academic goals, increased maturity, boredom, fertility and change in living situation. Conclusion: While there is overlap in several of the HRQoL concerns across the age span, it is important that HRQoL measures used with AYAs capture the diverse and unique psychosocial aspects of this developmental stage.